2013
DOI: 10.2174/1389557511313080007
|View full text |Cite
|
Sign up to set email alerts
|

ACAT Inhibitors: The Search for Novel Cholesterol Lowering Agents

Abstract: Increased level of serum cholesterol (hyperlipidemia) is the most significant risk factor for the development of atherosclerosis. Cholesterol levels are affected by factors such as rate of endogenous cholesterol synthesis, biliary cholesterol excretion and dietary cholesterol absorption. Acyl CoA: Cholesterol O-acyl transferases (ACAT) are a small family of enzymes that catalyze cholesterol esterification and cholesterol absorption in intestinal mucosal cells and maintain the cholesterol homeostasis in the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Consequently, the production of cytokines and cytolytic granules, and killing and proliferation of ACAT1-deficient CD8 + T cells are all significantly enhanced. Inhibiting ACAT1 has been demonstrated to offer benefits in treating cardiovascular and neurodegenerative diseases 6,7,26 , and we show that it can offer an additional benefit in treating cancer. ACAT1 inhibition can be used to complement current therapies such as immune checkpoint blockade 3,4,8,2730 because it acts through a different mechanism.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Consequently, the production of cytokines and cytolytic granules, and killing and proliferation of ACAT1-deficient CD8 + T cells are all significantly enhanced. Inhibiting ACAT1 has been demonstrated to offer benefits in treating cardiovascular and neurodegenerative diseases 6,7,26 , and we show that it can offer an additional benefit in treating cancer. ACAT1 inhibition can be used to complement current therapies such as immune checkpoint blockade 3,4,8,2730 because it acts through a different mechanism.…”
mentioning
confidence: 63%
“…ACAT1-deficient CD8 + T cells were better than wild-type CD8 + T cells at controlling melanoma growth and metastasis in mice. We used the ACAT inhibitor avasimibe, which was previously tested in clinical trials for treating atherosclerosis and showed a good human safety profile 6,7 , to treat melanoma in mice and observed a good antitumour effect. A combined therapy of avasimibe plus an anti-PD-1 antibody showed better efficacy than monotherapies in controlling tumour progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 This finding is interesting because the inhibition of ACAT is a well-known mechanism for reducing plasmatic circulating cholesterol levels since esterification is essential to cholesterol transport in lipoproteins. For the first time, we showed that cinnamon extract treatment induced a reduction in the liver content of esterified cholesterol that was accompanied by lower expression of ACAT, a key enzyme in the esterification of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Avasimibe is an inhibitor of ACAT, which is the primary enzyme of cholesterol esterification in CD8 + T cells. And it has been reported in treating atherosclerosis in clinical trials with good safety profile (T. Y. Chang, Li, Chang, & Urano, ; Llaverias, Laguna, & Alegret, ; Pal, Gandhi, Giridhar, & Yadav, ; Yang et al, ). Avasimibe treatment can enhance TCR clustering and T‐cell immunological synapse forming, then significantly potentiates the killing function of CD8 + T cells (Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%